Tafsir Misoginisme dan Inkonsistensi Birokrat (Implikasi Putusan MK No. 4/PUU-VIII/2010) - Abdul Wahid (The Constitutional Court of the Republic of Indonesia, 2011)
The verdict of Constitutional Court (MK) Number 4/PUU-VIII/2010 can be described as a verdict blocking chances for the civil servant (Pegawai Negeri Sipil) to represent himself/herself as the head of executive in the district such as governor, mayor, regent, and any others in the mayor general election (Pemilukada) because one of the prerequisites to be a civil servant must be followed by a resignation letter. This prerequisite cannot be considered as a form of discrimination and injustice for the civil servant, yet as a kind of protection through the strategic role of the civil servant. If the civil servant still keeps going on its track, as a bureaucracy devotee, then people’s civil rights must have been fulfilled.